Theorising Derecognition of Local Government Authorities as Political Injustice: The Effects of Technical Claims in Senegal's Forestry - Papa Faye (Conservation & Society, 2017)
Most developing-country governments have 'recognised' elected local governments (ELGs) by transferring to them the authority (e.g. rights and resources) over the forests within their jurisdiction. In practice, however, Forest Services are 'derecognising' ELGs – taking back these decentralised powers. This article shows that 'derecognition' is effectively a new 'recognition' dynamic in decentralised forest management in Senegal, in which Forestry officials and agents derecognise ELGs drawing upon technical claims. It also theorises derecognition as political injustice by demonstrating how the technical claims, although used in support of sustainable forest governance, cause political injustice through the following observed derecognition outcomes: 1) circumvention of ELGs that deprives them of the means to be responsive to local people (and thus disables them as democratic institutions); 2) subordination of the new participatory organisations created to receive the powers taken from ELGs to instrumental objectives of central forestry authorities; and 3) progressive privatisation of the forests that diminishes the democratic public domain.